Formation and modification of dispersions using Shirasu Porous Glass membranes - Goran Vladisavljevic (2015)
This chapter deals with the production, properties, and macrofluidic applications of Shirasu Porous Glass (SPG) membrane. The first section provides an overview of the membrane microfluidic processes used for production and modification of liquid-liquid and gas-liquid micro- and nano-dispersions, such as direct and premix membrane emulsification with and without phase inversion, membrane demulsification, membrane micromixing / direct precipitation and micro- and nano-bubbling. In the last section of this chapter, SPG membranes are compared with conventional homogenisers and microfluidic drop generators in terms of production rate, droplet size uniformity, and applied shear stresses. The second section deals with the fabrication of SPG membrane by spinodal decomposition in Na2O– CaO–Al2O3–B2O3–SiO2 type glass and morphological, mechanical, and hydrodynamic properties of SPG membrane. This chapter also covers modification of surface charge, contact angle and porosity of SPG membrane using different physical and chemical methods, such as deposition of silica nanoparticles onto membrane surface, coating with silicon resin, filling the pores with solvent-responsive polymer chains and chemical modification with silane coupling agents. The fourth section is focused on the effects of physical properties of the dispersed and continuous phase, operating parameters and membrane properties on the droplet size in direct and premix SPG membrane emulsification. In addition, the most common classes of micro- and nano-particles fabricated using SPG membrane were reviewed and their fabrication routes were discussed. It was concluded that a broad variety of different chemical and physicochemical processes can be combined with SPG membrane emulsification to convert droplets into uniform particle. The last section briefly discusses the generation of micro- and nano-bubbles using SPG membrane.